Hepatitis due to rickettsial fever: A case report - Kapil S Bainade; V A Kotrashetti; Vijay Baburao Sonawane; Soumya Ahuja; Shuchi Bhatarkar (Indian Journal of Child Health, 2021)
Rickettsial infections are re-emerging. In India, they are now being reported from several areas where they were previously unknown. Hepatitis is its rare complication in the pediatric population. Hepatitis is an inflammation of the liver. It can be self-limiting or can progress to fibrosis, cirrhosis, or liver cancer. In hepatitis, viruses are the most common cause in the world but other infections, toxic substances (e.g., alcohol, certain drugs), and autoimmune diseases can also be the etiology. Here we discuss hepatitis as a rare complication to Rickettsial fever in a 7-year-old male child who was diagnosed based on the serology and its clinical response to doxycycline. This etiology has not been well recognized and has been rarely reported in Indian Literature.